AN ANALYSIS OF THE EFFECT OF CREDIT RISK MANAGEMENT ON PROFITABILITY OF COMMERCIAL BANKS IN KENYA - WANJOHI, ANTHONY; BAIMWERA, MR. BERNARD (International Journal of Finance and Accounting, 2016)
Purpose: The purpose of this study was to analyse the effect of credit risk management on profitability of commercial banks in Kenya. Methodology: This study adopted a descriptive design. The study targeted a population of all the 44 commercial banks with the exception of Charterhouse bank which is under statutory management. The sample of this study was 86 employees out of a possible 30,056 employees from the 43 commercial banks. The sample of 86 was generated by purposively sampling two employees from each bank. One employee was a manager from the finance department while the other employee was a manager from the credit risk department. The questionnaire comprised of closed ended questions. Secondary data for ROA was identified. SPSS was used to produce frequencies, descriptive and inferential statistics which was used to derive conclusions and generalizations regarding the population. Regression analysis was also used to show the sensitivity of profitability, ROA to various independent variables. Results: The study findings indicated that credit department had various checks during loan credit review. The credit department always checked at the character of the borrower, collateral of the borrower, capacity of the borrower, capital of the borrower, conditions and controls during credit review. Results indicated that the banks had credit appraisal practices, credit monitoring practices, debt collection practices and credit risk governance practices in place. Regression results indicated that there was a positive and significant relationship between credit appraisal, credit monitoring, debt collection and credit risk governance practices and profitability of commercial banks. Unique contribution to theory, practice and policy: The study concluded that credit appraisal, credit monitoring, debt collection and credit risk governance practices had a positive effect on the profitability of commercial banks. The study recommends that the banks should continue emphasizing on the effective credit appraisal, credit monitoring, debt collection and credit risk governance practices so as to enhance maximum profits in banks.